Comparison Between Trot and Wave Gait Applied in Quadruped Robot - Feriyonika Feriyonika; Noor Cholis Basjdaruddin; Martin Martin (ELKHA : Jurnal Teknik Elektro, 2023)
A Quadruped robot is a type of robot that moves on four legs and has a structure like a four-legged animal. The quality of movement based on mechanics and movement patterns on quadruped robots tends to have poor movement patterns. This study investigates the best movement between trot and wave gait by comparing the speed performance, stopping distance accuracy, and the tilt of the robot body angle. To minimize the influence of the mechanical quality of the robot, this study used two robots based on the type of servo used (based on the SG90 and MG995 servos). In this study, the motion pattern based on Trot and Wave gait is realized using Inverse Kinematics and Polynomial trajectory on each leg. The verification experiment showed that the Wave gait has better in both the robot body angle and distance error. In contrast the Trot gait has better in speed.